Current Issues Pertaining Gender-Based Violence in Sri Lanka (Proceedings of the World Conference on Women’s Studies, 2021)
A qualitative study was conducted to obtain an understanding of the current attitudes, beliefs, and other related issues related to gender in Sri Lanka. The study used interviews, mini-interviews, and Focused Group Discussions (FGD) for this purpose. The study consisted a few different samples and the majority of the sample was drawn from the health sector. The study explored different cultural regions of Sri Lanka via the FGDs. The objective of the study was to provide insight in to the current situation of gender-based violence (GBV) and related issues in Sri Lanka. The study yielded interesting results which could be explored by future researchers. The salient outcomes were that the strong role of economic factors in GBV was identified, the effect of micro credit facilities and increased substance abuse on GBV were identified.  In addition to this insight was gained to the possible issues related to GBV in different cultures in Sri Lanka and GBV in a few industrial settings in Sri Lanka.
Keywords: Gender-Based Violence (GBV); Economic factors; Culture; Micro Credit